A RARE CASE OF HYPONATREMIA AS A LEADING SIGN OF EMPTY SELLA SYNDROME - Rahmawati , Yuni; Tarigan, Tri Juli Edi (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Hyponatremia is a common electrolyte disturbance that can be life-threatening. Careful evaluation of hyponatremia may reveal significant underlying conditions and may lead to the diagnosis of a rare multiple hormone deficiency, with detrimental consequences for the patient if left untreated. We present an interesting case of a patient who presented with symptoms of chronic hyponatremia, and the results of the examination led us to the discovery of partial empty sella syndrome as the aetiology. CASE A 61-year-old female presented with a six-year history of general weakness, nausea, vomiting and cold intolerance. She was diagnosed with hyponatremia and has routinely received sodium supplementation therapy. However, the patient’s complaints have worsened over the past year. There is history of severe vaginal bleeding and shock during childbirth 22 years ago, which required a hysterectomy to be performed. Physical examination showed no abnormalities. Laboratory data showed severe hyponatremia with a serum sodium of 115 meq/L and low serum osmolality, but urine osmolality and urine sodium were elevated. Renal examination showed no abnormality. Thyroid function showed a low FT4 level at <0.4ng/dL (Reference Value [RV]: 0.7-1.48 ng/dL) and normal TSH at 1.882uIU/mL (RV: 0.35-4.94 uIU/mL). A low AM cortisol level of <1.0 mcg/dL (RV: 3.7–19.4 mcg/dL), normal adrenocorticotropic hormone (ACTH) level of 18.9pg/mL (RV: 7.2-63.3 pg/mL) suggested secondary adrenal insufficiency. She had low LH (6.6 mIU/mL), low FSH (11.7 mIU/mL) and low estradiol (5 pg/mL). The brain magnetic resonance imaging (MRI) confirmed the diagnosis of partial empty sella. Treatment with steroids and levothyroxine led to symptoms and laboratory resolution in a few months. CONCLUSION Empty sella syndrome is a rare pituitary condition that can be primary or secondary. It can potentially cause hypopituitarism that may be symptomatic or asymptomatic. This case emphasises the need for a comprehensive work-up of hyponatremia, awareness of secondary adrenal insufficiency, panhypopituitarism and recognition of the life-threatening potential of partial empty sella syndrome if left untreated.